Analysis of Nucleotide Sequences of the 16S rRNA Gene of Novel Escherichia coli Strains Isolated from Feces of Human and Bali Cattle - Suardana, I Wayan (Journal of Nucleic Acids, 2014)
Livestock especially cattle are known as a main reservoir of Escherichia coli O157:H7. This bacterium is considered as a pathogenic agent characterized by producing toxins, which are familiarly known as Shiga-like toxin-1 (Stx1) and Stx2. The aim of this work was to analyse the novel sequence of the 16S rRNA gene of strains isolated in this study in order to know the phylogenetic relationships between these sequences and those between the sequences of bacteria available in databanks. The results of this analysis showed that the strains KL-48(2) and SM25(1) that originated from human and cattle feces, respectively, are closely related among them and with respect to E. coli EDL 933, E. coli Sakai, E. coli ATCC 43894, E. coli O111:H-, E. coli O121:H19, E. coli O104:H4, and Shigella sonnei with more than 99% similarity values.